Preparation and Characterization of Nano-Barium Titanate Based on Glass Fiber Filter and its Application in Preconcentration of Heavy Metals in Environmental Water - Li, Yan; Zhang, Dong (Asian Journal of Chemistry, 2013)
Nano-barium titanate based on glass fiber filter (GFBT) was successfully prepared by sol-gel method and characterized using XRD and SEM. The adsorptive potential of GFBT for heavy metal ions, such as lead, cadmium, zinc, nickel, copper and silver, was investigated. The results showed that the nano-barium titanate could crystal based on glass fiber, gaining a new block adsorbent like a leaf. The lead, cadmium, zinc, nickel, copper and silver ions were quantitatively retained at pH 5-9; their adsorption capacities of GFBT for lead, cadmium, zinc, nickel, copper and silver ions were 155.93, 22.38, 35.98, 3.97, 81.92 and 15.32 mg/g, respectively. The adsorbent can be regenerated completely by elution with 1 mol/L HNO3. The method has been applied to the simultaneous preconcentration of trace amounts of lead, cadmium, zinc, nickel, copper and silver in environmental water with satisfactory results.